DEVELOPMENT OF THE CAST MOLDING MANUFACTURE TECHNOLOGY ON GASIFIED MODELS - I. M. Tikhomirova; E. V. Klimenok; A. N. Krutilin (Литьë и металлургия)
In the course of the work the basic details of foundry equipment were developed. On the basis of mathematical modeling of casting processes the filling and solidification «Suspension of PMD» were analyzed, the most portable places of pore formation were identified. Basic details of foundry equipment and process parameters were adjusted.